Exercise heart rate recovery assessment of the cardiac autonomic nervous system in workers occupationally exposed to lead - Uğur Nadir Karakulak; Ömer Hınç Yılmaz; Engin Tutkun; Meşide Gündüzöz; Banu Evranos; Emine Ercan Onay; Mehmet Aytürk; Müjgan Tek Öztürk (Türk Kardiyoloji Derneği Arşivi, 2016)
Objective: The aim of the present study was to assess cardiac autonomic function via indices of exercise heart rate recovery (HRR) in workers occupationally exposed to lead. Methods: A total of 98 lead-exposed workers and 98 healthy controls were enrolled. All underwent exercise testing and transthoracic echocardiography. HRR indices were calculated by subtracting 1st - (HRR1), 2nd- (HRR2), and 3rd-minute (HRR3) heart rates from maximal heart rate (HR). Exercisetest parameters– HRR in particular– were compared betweengroups, and correlation analysis of blood, 24-hour urine lead levels, and test parameters was performed. Results: Baseline demographic and clinical characteristics were found to be similar between groups. Mean HRR1 (26.2+-3.6 vs 29.0+-4.1 bpm, p<0.001), HRR2 (42.6+-3.9 vs 46.9+-3.7 bpm, p<0.001), and HRR3 (56.6+-4.5 vs 61.8+-4.3 bpm, p<0.001) values were significantly lower in the leadexposed group than in the healthy controls. HRR1 was found to be significantly correlated with blood (r: -0.415;p<0.001) and 24-hour urine lead levels (r: -0.446; p<0.001). HRR2 and HRR3 were significantly correlated with 24-hour urine lead level (r: -0.396; p<0.001 and r: -0.233; p=0.021, respectively). Conclusion: Lead-exposed workers had lower HRR indices than normal subjects. Blood and 24-hour urine lead levels were significantly associated with HRR indices. Cardiac autonomic functions may be affected by exposure to lead, and those occupationally exposed should be closely followed for adverse cardiovascular outcome.